Steady state and time resolved fluorescence quenching and chemical modification studies of a lectin from endophytic fungus fusarium solani - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Journal of Fluorescence, 2010)
The solute quenching studies of a lectin from endophytic fungus Fusarium solani were carried out using different quenchers such as acrylamide, succinimide, potassium iodide and cesium chloride. The lectin showed emission maximum at 348 nm indicating relative exposure of tryptophan. The quenchable fraction of the fluorophore was 100% with acrylamide, whereas it was only 50% with succinimide. The ionic quenchers iodide and cesium showed opposite effects at different pH. In the case of cesium, raising the pH resulted in increased quenching and accessibility of typtophan residue, while the iodide showed just opposite effect. These studies showed that the single tryptophan residue of the lectin (per monomer) is relatively exposed, and might be in the vicinity of positively charged amino acid residues. Various amino acids of the F. solani lectin were modified using different reagents to obtain information about the hemagglutinating site. The chemical modification studies suggested tyrosine residues can be modified using N-acetylimidazole, which results in complete loss of hemagglutination activity of the lectin. Kinetics of chemical modification suggested involvement of only 2 tyrosine residues. Modification of arginine, cysteine, histidine, lysine, aspartate, glutamate and tryptophan did not result in loss of hemagglutinating activity of the lectin.
Keywords: Chemical modification; fluorescence; Fusarium; Lectin; Quenching; Time-resolved